Occupational asbestos exposure and survival among lung cancer patients. (May 2023) - Noelle, Hugo; Pérol, Olivia; Pérol, Maurice; Avrillon, Virginie; Belladame, Elodie; Fayette, Jérôme; Fournié, Françoise; Swalduz, Aurélie; Dessemon, Juliette; Blay, Jean-Yves; Neidhardt, Eve-Marie; Saintigny, Pierre; et al.
Highlights: Overall survival in occupationally asbestos exposed LC patients may be decreased. No interaction between tobacco smoking and asbestos exposure on survival. Screening of occupational exposures should be systematic in lung cancer patients. Abstract: Objective: This study investigated the association between occupational asbestos exposure (OAE) and survival in patients with histologically confirmed lung cancer (LC). Methods: This monocentric study was conducted in the Comprehensive Cancer Centre Léon Bérard, Lyon, France. A systematic screening has been in place since 2014 for occupational exposure to carcinogens using a self-assessment questionnaire sent to all patients newly diagnosed with histologically confirmed LC identified through the multidisciplinary LC board from 2014 to 2019. When the physician suspected a work-related exposure from the questionnaire including job history, an occupational cancer consultation was carried out to detail carcinogen exposures and assess if the LC was work-related. Demographics, clinical characteristics and survival data were extracted from medical records. The association between asbestos exposure and overall survival (hazard ratio and 95% confidence intervals) was estimated by Cox proportional hazards regression. Results: Overall, 702 patients were eligible to the present study, including 180 patients with OAE. In the crude analysis, LCs assessed as moderately or highly attributable to OAE were associated with decreased overall survival (HR = 1.32, 95 %CI 1.04–1.67) compared to LC without OAE or with a low degree of imputability to OAE (median follow-up 28.8 months). After adjustment for confounding (age at diagnosis, smoking status, stage, brain metastasis at diagnosis, and histology), the association of OAE with overall survival was no longer statistically significant (HR = 1.21, 95 %CI 0.94–1.56). Conclusion: Overall survival in occupationally asbestos exposed LC patients may be decreased in comparison with non-exposed LC patients, warranting further investigations in larger studies.